The effect of water on the validity of Löwenstein's rule - Heard, Christopher J; Grajciar, Lukáš; Nachtigall, Petr (Chemical science, 2019)
The common understanding of zeolite acidity is based on Löwenstein's rule, which states that Al-O-Al aluminium pairs are forbidden in zeolites. This rule is generally accepted to be inviolate in zeolites. However, recent computational research using a 0 K DFT model has suggested that the rule is violated for the acid form of several zeolites under anhydrous conditions [Fletcher et al., Chem. Sci., 8, (2017), 7483]. The effect of water loading on the preferred aluminium distribution in zeolites, however, has so far not been taken into account. In this article, we show by way of ab initio molecular dynamics simulations that Löwenstein's rule is obeyed under high water solvation for acid chabazite (H-CHA) but disobeyed under anhydrous conditions. We find that varying the water loading in the pores leads to dramatic effects on the structure of the active sites and the dynamics of solvation. The solvation of Brønsted protons in the surrounding water was found to be the energetic driving force for the preferred Löwenstein Al distribution and this driving force is absent in non-Löwenstein (Al-O(H)-Al) moieties. The preference for solvated protons further implies that the catalytically active species in zeolites is a protonated water cluster, rather than a framework Brønsted site. Hence, an accurate treatment of the solvation conditions is crucial to capture the behaviour of zeolites and to properly connect simulations to experiments. This work should lead to a change in modelling paradigm for zeolites, from single molecules towards high solvation models where appropriate.